Misconceptions and Difficult Concepts as Determinant of Students’ Academic Engagement and Retention in Physics - Barnabas Obiaje Ellah; Emmanuel Edoja Achor; Joy Okache Omaga (Faculty of Teacher Training and Education, Universitas Muhammadiyah Surakarta, 2022)
The study determined the predictive power of students’ misconceptions and difficult concepts in physics on academic engagement and retention. The study adopted a correlational survey research design. The population comprised 3148 science students in Benue State. The sample was 650 science students. Six research questions were answered and six null hypotheses were tested. The instruments for data collection were Physics Difficult Concepts Retention Test (PDCRT), Physics Academic Engagement Scale (PAES), and Physics Students’ Misconceptions Identification (PSMI). The PDCRT, PAES, and PSMI were faces validated and PDCRT was also content validated. An estimate of internal consistency was obtained through Cronbach’s Alpha for PAES and Kuder-Richardson (K-R21) for PDCRT. The coefficient of internal consistency was 0.73 for PAES and 0.88 for PDCRT. Regression analysis was used for data analysis. It was spotlighted that students’ misconceptions, as well as difficulty levels in Physics, significantly predicted academic engagement. However, students’ misconceptions, as well as difficulty levels, do not significantly predict retention in Physics. It was also found that students’ misconceptions and difficulty levels jointly significantly predicted students’ academic engagement in Physics. Similarly, the combination of students’ misconceptions and difficulty levels significantly predicted retention in physics. It was recommended among others that Physics teachers should use instructional strategies that allow self-directed learning that could give emotional safety, reduce misconceptions and enhance academic engagement. Physics teachers should guide students using systematic procedures so that they acquire relevant skills essential for successful learning interplay to reduce the level of difficulty in understanding Physics concepts and enhance retention.